2011
DOI: 10.1038/emboj.2011.352
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative modelling of amyloidogenic processing and its influence by SORLA in Alzheimer's disease

Abstract: The extent of proteolytic processing of the amyloid precursor protein (APP) into neurotoxic amyloid-b (Ab) peptides is central to the pathology of Alzheimer's disease (AD). Accordingly, modifiers that increase Ab production rates are risk factors in the sporadic form of AD. In a novel systems biology approach, we combined quantitative biochemical studies with mathematical modelling to establish a kinetic model of amyloidogenic processing, and to evaluate the influence by SORLA/SORL1, an inhibitor of APP proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 38 publications
10
82
0
Order By: Relevance
“…To more rigorously test the relevance of PACS1 for SORLA transport in neurons, we established a novel cell model by using the neuroblastoma cell line SH-SY5Y, which stably overexpresses the human SORLA and APP695 transgenes (SY5Y-A/S). SH-SY5Y cells express low levels of endogenous SORLA, but these levels are negligible when SORLA transgenes are overexpressed (21). When transiently transfected with a siRNA directed against endogenous PACS1 (without PACS1), expression of the adaptor was strongly reduced compared to that in SY5Y-A/S cells transfected with a scrambled control siRNA (with PACS1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To more rigorously test the relevance of PACS1 for SORLA transport in neurons, we established a novel cell model by using the neuroblastoma cell line SH-SY5Y, which stably overexpresses the human SORLA and APP695 transgenes (SY5Y-A/S). SH-SY5Y cells express low levels of endogenous SORLA, but these levels are negligible when SORLA transgenes are overexpressed (21). When transiently transfected with a siRNA directed against endogenous PACS1 (without PACS1), expression of the adaptor was strongly reduced compared to that in SY5Y-A/S cells transfected with a scrambled control siRNA (with PACS1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Willnow and colleagues ruled out a role for SORLA in retrograde transport of internalized APP but proposed an alternate model in which SORLA acts as a retention factor for APP at the Golgi, impeding its exit and subsequent sorting to the plasma membrane and endocytic organelles (4). T en, using inducible SORLA expression and siRNA knockdown combined with mathematical modeling of APP processing, they proposed yet another model in which SORLA prevents APP oligomerization, thus reducing the ef ciency of APP processing by α-secretase and BACE1 (8). Alternatively, Lah and colleagues have suggested that SORLA reduces BACE1 processing of APP and Aβ production by escorting APP to the endocytic recycling compartment and away from early and late endosomes where internalized APP undergoes amyloidogenic processing (9).…”
Section: Sorla Modulates App Processingmentioning
confidence: 96%
“…S6). A peptide containing this sequence (termed Ab [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] bound to the SORLA VPS10P domain with a concentration dependency indistinguishable from that of Ab 40 (Fig. 6B, diamond symbols).…”
Section: Sorla Binds To Soluble Ab Through Its Vps10p Domainmentioning
confidence: 99%